Treatment of a femoral septic nonunion in a dog with interlocking nail stabilization associated to corticospongious bone autograft and greater omentum flap: case report - Menezes, M. P. [UNESP]; Costa, R. C. [UNESP]; Conceicao, M. E. B. A. M. [UNESP]; Minto, B. W. [UNESP]; Dias, L. G. G. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Chronic septic bone nonunion requires a well-designed therapeutic planning, demanding a multimodal treatment to achieve bone consolidation and elimination of infection. A successful case of an association of the major omentum flap with surgical stabilization with an interlocking nail for treatment of a femoral septic nonunion in dog is reported. The patient had partial functional return of the limb 30 days after surgery, negative bacterial culture with radiographic signs of bone healing and total functional return of the limb at 90th days after the surgical procedure.
Keywords: complication; orthopaedics; osteomyelitis; planning